Improving Gen Z Employee Retention through Work–Life Balance with Employee Engagement as a Mediating Variable - Nardi, Fransiskus Rio; Ginting, Sunardi (Manunggal Halim Jaya, 2026)
A high employee turnover rate can lead to substantial losses in both productivity and costs for a company. Therefore, organizations must prioritize employee retention and consider the factors that influence it. This study examines the effect of work–life balance on employee retention, the effect of employee engagement on employee retention, and the mediating role of employee engagement in the relationship between work–life balance and the retention of Generation Z employees working in coffee shops in Pontianak. Data were collected using Google Forms and a snowball sampling technique. The data were analyzed using WARPPLS 7.0, with 221 coffee shop employees in Pontianak serving as respondents. The results show that work–life balance has a significant positive effect on both employee engagement and employee retention. Furthermore, employee engagement has a significant positive effect on employee retention and significantly mediates the relationship between work–life balance and employee retention. The findings of this study contribute to the development of knowledge, particularly in human resource management, by providing insights into the relationship between work–life balance and employee retention, as well as the mediating role of employee engagement.